Accuracy of 12 Lead ECG For Diagnosis of Posterior Myocardial Infarction Taking 15 Lead ECG As Gold Standard - Panezai, Sikander Azeem; Azim, Waqar; Kakar, Kaleemullah; khan, Alamzeb; Tareen, Sehrish Ghani; Tareen, Zarghoona (Journal of Medical Biomedical and Applied Sciences, 2018)
INTRODUCTIONThe acute management of ST-elevation myocardial infarction (STEMI) is based on interpretation of the ECG. Thisis typically undertaken by doctors in the emergency department (ED) and acute medical unit. Increasingly, the ECGdiagnosis is being made by paramedics, allowing them to pre-alert the ED or even initiate thrombolytic therapy inregions where primary angioplasty is unavailable. Identification of ST-segment elevation or presumed new left-bundlebranch block in combination with a history of cardiac chest pain results in prompt initiation of reperfusion therapy.SUBJECT AND METHODA cross sectional study was done at Cardiology Department, Bolan Medical College, Quetta. Total duration was from01/02/2018-30/07/2018. 196 patients were recruited from Out Patient Department and Emergency Department of BolanMedical Complex, Quetta on the basis of inclusion/exclusion criteria, that is all patient with chest pain and age >18 and< 70 with posterior MI as per operational definition presenting within 12 hours of symptoms were included and allpatients with underlying LBBB on ECG, PPM and paced rhythm on ECG and pericardial effusion were excluded asthey are effect modifiers and bring bias in study.RESULTSTotal 196 patients were included in the study according to the inclusion criteria of the study. Mean age (years) in thestudy was 40.28+14.38 whereas there were 123 (62.8) male and 73 (37.2) female patients in the study. The diagnosticaccuracy, sensitivity, specificity, PPV and NPV of 12 lead ECG for diagnosis of posterior myocardial infarction taking 15lead ECG as gold standard was 82.14%, 87.12%, 57.58%, 91.03% and 47.50% respectively.CONCLUSIONThe study concludes that diagnostic accuracy of 12 lead ECG for diagnoses of posterior wall myocardial infarction washigh. The high sensitivity identified more patients to be re vascularized early.